The Influence Of Profitability, Leverage, Firm Size, Capital Structure, Intellectual Capital On Firm Value (Case On Industrials Sector Companies Listed On The Indonesia Stock Exchange For The 2018-2021 Period) - Kristanti, Farida Titik; Divando, Ghalib Faris (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to determine how firm value is affected by profitability, leverage, firm size, capital structure, and intellectual capital. This quantitative study makes use of the panel data regression technique with Eviews 12 software. Companies in the industrial sector listed on the Indonesia Stock Exchange between 2018 - 2021 period. The study's overall sample, which included 13 businesses over the course of the four time periods, yielded a total of 52 observations. According to the study's findings, capital structure has a significant positive impact on the firm value of the listed industrial sector companies on the Indonesian Stock Exchange, while profitability, leverage, firm size, and intellectual capital have no effect on the firm value of the industrial sector companies listed on the Indonesian Stock Exchange in 2018–2021.